2023
DOI: 10.1007/s11101-023-09864-1
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge on genus Bassia All.: a comprehensive review on traditional use, phytochemistry, pharmacological activity, and nonmedical applications

Abstract: Bassia All. is a genus from the Amaranthaceae family, which was created by merging selected species belonging to the former Bassia and Kochia genera with those classified to Chenolea, Londesia, Kirilowia and Panderia. The reorganised Bassia genus currently comprises around 20 species, which are annual herbs or perennial subshrubs native to Eurasia and Africa. Bassia plants are well known for their therapeutic applications in folk medicine and traditional medical systems, and they are also used for nonmedical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 187 publications
1
1
0
Order By: Relevance
“…In the present study, UPLC-ESI–Qtof-MS analysis has allowed for the comprehensive characterization of the BIEE metabolites via an untargeted approach ( Figure 9 ). In total, 40 metabolites were annotated mostly belonged to two main chemical classes, viz ., flavonoids and lipids, in line with the reported literature [ 31 ]. The identification strategy of the detected metabolites was based on their retention times, experimental m / z , molecular formulas, mass errors and their MS 2 fragments, as shown in ( Table 3 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, UPLC-ESI–Qtof-MS analysis has allowed for the comprehensive characterization of the BIEE metabolites via an untargeted approach ( Figure 9 ). In total, 40 metabolites were annotated mostly belonged to two main chemical classes, viz ., flavonoids and lipids, in line with the reported literature [ 31 ]. The identification strategy of the detected metabolites was based on their retention times, experimental m / z , molecular formulas, mass errors and their MS 2 fragments, as shown in ( Table 3 ).…”
Section: Resultssupporting
confidence: 91%
“…In the present study, UPLC-ESI-Qtof-MS analysis has allowed for the comprehensive characterization of the BIEE metabolites via an untargeted approach (Figure 9). In total, 40 metabolites were annotated mostly belonged to two main chemical classes, viz., flavonoids and lipids, in line with the reported literature [31]. The identification strategy Methoxy flavonoids such as isorhamnetin and its glycosides have also been identified in the BIEE in agreement with the reported literature [35].…”
Section: Metabolites Profiling Of B Indica Etoh Extract Via Uplc-esi-...supporting
confidence: 89%
“…The results of the current study were similar to the reported phytochemical profile of other plants of the genus Bassia like B. scoporia, and B. muricata, etc. [10,17,44]. The presence of phenols and flavonoids makes B. indica a plant of therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…: Kochia indica Wight] belongs to the family Amaranthaceae [9]. This family includes a large number of halophytes that are well-known for their therapeutic applications in traditional medical systems and are used for infected skin wounds, internal worms, fungal infections, renal and rheumatic disorders [10] as a cardiotonic [11], anti-inflammatory, and antioxidant [12]. B. indica is an annual herb found in Egypt, India, Pakistan, Northern Africa, Saudi Arabia, and other countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are considered a rich reservoir of bioactive substances with therapeutic potential because of their chemical diversity [ 96 , 97 ]. Generally, drug discovery from plants for the treatment of BU, starts from an ethnobotanical survey to provide background information regarding the type of plant and plant part used, formulation (such as decoction, trituration, infusion, powders, maceration, pomade), and mode of administration (bandage, dermal) [ 98 ].…”
Section: Compounds Isolated From Indigenous African Plants For the Tr...mentioning
confidence: 99%